2016
DOI: 10.3762/bjoc.12.30
|View full text |Cite
|
Sign up to set email alerts
|

Enabling technologies and green processes in cyclodextrin chemistry

Abstract: SummaryThe design of efficient synthetic green strategies for the selective modification of cyclodextrins (CDs) is still a challenging task. Outstanding results have been achieved in recent years by means of so-called enabling technologies, such as microwaves, ultrasound and ball mills, that have become irreplaceable tools in the synthesis of CD derivatives. Several examples of sonochemical selective modification of native α-, β- and γ-CDs have been reported including heterogeneous phase Pd- and Cu-catalysed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Ball mill assisted syntheses are good alternatives to overcome solubility difficulties in syntheses or isolation of natural compounds from vegetables using CDs [910]. Environmentally benign synthetic methods of CD derivatives have been recently reviewed [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Ball mill assisted syntheses are good alternatives to overcome solubility difficulties in syntheses or isolation of natural compounds from vegetables using CDs [910]. Environmentally benign synthetic methods of CD derivatives have been recently reviewed [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Even after 75 min, we did not see the formation of the expected product. Finally, we attempted the ring opening of epoxide using ball milling, a mecanosynthesis technique widely used in green chemistry [12,13]. Very recently, Cravotto et al [14] described ring opening of low-boiling epoxides by CDs under high-energy ball milling conditions and in the presence of NaOH, leading to well-known HP-β-CD, HP-γ-CD and epichlorhydrin cross-linked CDpolymers.…”
Section: Scheme 1 Epoxidation Reaction Of Methyl Oleatementioning
confidence: 99%
“…The different strategies envisaged to carry out the opening reaction of the epoxide obtained by CDs is described. Indeed, activation modes such as ultrasound [8,9], microwaves [10,11], or mechanochemistry [12] are considered as useful green tools for the chemical modification of cyclodextrins. Cravotto et al reported some works where ball milling is used to obtain well-known CD derivatives but under green and solventless conditions and with better yields [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the production of cyclodextrins (CDs), the main substrates used are starches and their derivatives. The catalytic action of the enzyme cyclomaltodextrin‐glucan transferase (CGTase) originates a mixture of malto‐oligaccharides of cyclic structure, mainly α‐CD (cyclohexamylose), β‐CD (cycloheptamylose) and γ‐CD (cyclooctamylose), and minimal amounts of larger CDs . The CDs produced from the starch by the action of CGTase have high added value and present numerous possibilities of industrial applications due to its capacity to form inclusion complexes with organic and inorganic molecules.…”
Section: Introductionmentioning
confidence: 99%